Developing a dual track startup framework for construction technology ventures; integrating business formation and product development; a blueprint for civil engineer entrepreneurs - Alzokani, Mohamad Omar (My University, 2025)
The construction industry is undergoing a slow but necessary transformation driven by the need to address inefficiencies, budget overruns, regulatory complexities, and technological stagnation. While innovation in construction technology (ConTech) has the potential to resolve many of these challenges, most existing startup methodologies are not adequately equipped to support founders operating in this highly regulated, fragmented, and slow-to-adopt sector. This thesis investigates how civil engineers, typically non-technical founders in the startup sense, can navigate the entrepreneurial landscape and build viable startups that respond to construction-specific demands. Through a mixed-methods approach combining qualitative interviews with six industry experts and in-depth analysis of two ConTech startup case studies and a literature review, this research evaluates the strengths and limitations of three dominant startup frameworks: the Lean Startup, The Startup Owner’s Manual, and Disciplined Entrepreneurship. Findings reveal that while each methodology offers valuable components, they often assume digital-first models, linear progression, and technical co-founders, assumptions that conflict with the real-world constraints of ConTech ventures. In response, this study introduces the Refined ConTech Startup Blueprint, a dual-track framework that integrates product/service development with business formation and operations. To validate the blueprint, it was implemented in a real-world context through the launch of a new startup, Permitt.ai, built from idea to execution using the proposed methodology. This practical application demonstrates the blueprint’s effectiveness in addressing key challenges such as regulatory compliance, team formation, product-market fit, and early-stage traction. By offering a structured yet adaptable roadmap grounded in empirical insight and field testing, the thesis contributes to the growing body of knowledge in entrepreneurship within engineering disciplines and provides practical guidance for civil engineers seeking to launch startups that catalyze meaningful change in the construction industry.
Keywords: Construction Technology, Startup Methodologies, Civil Engineers, Innovation, Lean Startup, ConTech, Disciplined Entrepreneurship, Business Formation, Permitt.ai, Startup Blueprint